Blood based immune biomarkers associated with clinical frailty scale in older patients with melanoma receiving checkpoint inhibitor immunotherapy - Estelle Tran Van Hoi; Saskia J. Santegoets; Simon P. Mooijaart; Diana Van Heemst; Asli Özkan; Elizabeth M. E. Verdegaal; Marije Slingerland; Ellen Kapiteijn; Sjoerd H. van der Burg; Johanneke E. A. Portielje; Marij J. P. Welters; Nienke A. de Glas (Immunity & Ageing)
Abstract Introduction Immunotherapy with checkpoint inhibition (ICI) is increasingly prescribed to older patients with cancer. High age, especially in combination with frailty, has been associated to immune senescence, which is the age-related decline in immune function, thereby possibly hindering ICI effectiveness. This cross-sectional study aimed to assess whether blood cell immune senescence markers are associated with age, frailty and response to anti-PD-1 treatment in older patients with metastatic melanoma. Methods In a prospective observational study, sixty patients with stage IIIC or IV melanoma undergoing anti-PD1 treatment were categorized into young (< 65 years; n = 22), old (> 65 years) without frailty (n = 19), and old with frailty (n = 19). In-depth immune cell phenotyping was performed in baseline blood samples (prior to treatment) using multispectral flow cytometry and compared between groups and with immunotherapy treatment response. Antigen-presenting cell capacity was evaluated using mixed lymphocyte reaction and T cell proliferative potential was assessed using PHA proliferation assay. Results No significant differences in treatment response rates were observed across age groups. Older patients, irrespective of frailty, showed lower levels of naïve CD8 + T cells, with the old and frail group also exhibiting reduced tissue-resident effector memory CD8 + T cells and CD8 + mucosal associated invariant T (MAIT) cells. These differences were not associated with treatment outcomes. T cell proliferation and antigen-presenting cell capacities did not differ across groups. Conclusion Several ageing and frailty associated changes were detected among circulating immune cells in blood but were not associated with response to immunotherapy in our study. While these findings suggest that the level of frailty and ageing may not necessarily preclude the efficacy of ICI therapy, further investigation is needed to fully understand the impact of frailty and ageing on immunotherapy.